A reflection of a pedagogic approach in an engineering course - Ferreira, Manuel Eduardo Cardoso (2019)
This paper focused the subject of engineering education for Energy Conversion, last year of the the Integrated Master in Mechanical Engineering Master Course of University of Minho. This curricular unit focus on the fossil fuel resources and combustion. Previous study, carried out by one of the authors, show that a final project can be used as a lever for students’ awareness and to understand the renewable energy sources. Also, it allowed students to identify several challenges to be addressed in the future. The present study goes further and the aim behind it is to understand students’ concerns in this area. To do so, both quantitative and qualitative approaches were used. Quantitative approach, by taking account of the results of an inquiry questionnaire applied to obtain students’ perceptions towards the implementation of this teaching approach and assessment methodology. Qualitative approach, to complement the quantitative findings, using both written project report and oral presentations, to perceive students’ awareness, knowledge and sustainability in Energy and Environment topic. So, it will be possible to understand which topic was preferred, why this particular topic was chosen, how the topic was addressed, if students identified challenges and opportunities, and learn from developing this projects, among others.